Luminescence and photo‐thermally stimulated defect creation processes in PbWO4:Mo, La, Y (PWO III) crystals. Issue 10 (14th July 2015) - Auffray, E.; Korjik, M.; Laguta, V. V.; Zazubovich, S.
<x xml:space="preserve">Abstract</x> Photoluminescence, thermally stimulated luminescence and electron spin resonance are studied for a PbWO4 crystal grown by the Czochralski method at Bogoroditsk Technical Chemical Plant, Russia from the melt with a precise tuning of the stoichiometry and co‐doped with La3+, Y3+, and Mo6+ ions. Photo‐thermally stimulated processes of electron and hole centers creation under selective UV irradiation of the crystal in the 3.5–5.0 eV energy range and 85–205 K temperature range are clarified and the optically created electron and hole centers are identified. The electrons in this crystal are found to be mainly trapped at the (MoO4)2− groups as well as at the (WO4)2– groups located close to single La3+ and Y3+ ions, producing electron (MoO4)3–, {(WO4)3– – La3+} and {(WO4)3– – Y3+} centers. The holes are mainly trapped at the regular oxygen ions O2– located close to La3+ and Y3+ ions associated with lead vacancies, producing the O−(I)‐type centers, or to single Mo ions, producing the O−(II) centers. No evidence of single‐vacancy‐related centers has been observed. The data obtained indicate a small concentration of single (non‐compensated) oxygen (VO) and lead (VPb) vacancies as the traps for electrons and holes, respectively, which explains more favorable scintillation characteristics of the PbWO4:Mo, La, Y crystal as compared with the earlier studied PbWO4:Mo, La and PbWO4:Mo, Y crystals.